Meta‐analysis on shift work and risks of specific obesity types. (4th October 2017) - Sun, M.; Feng, W.; Wang, F.; Li, P.; Li, Z.; Li, M.; Tse, G.; Vlaanderen, J.; Vermeulen, R.; Tse, L. A.
Summary: Aims: This systematic review and meta‐analysis evaluated the associations between shift work patterns and risks of specific types of obesity. Methods: PubMed was searched until March 2017 for observational studies that examined the relationships between shift work patterns and obesity. Odds ratio for obesity was extracted using a fixed‐effects or random‐effects model. Subgroup meta‐analyses were carried out for study design, specific obesity types and characteristics of shift work pattern. Results: A total of 28 studies were included in this meta‐analysis. The overall odds ratio of night shift work was 1.23 (95% confidence interval = 1.17–1.29) for risk of obesity/overweight. Cross‐sectional studies showed a higher risk of 1.26 than those with the cohort design (risk ratio = 1.10). Shift workers had a higher frequency of developing abdominal obesity (odds ratio = 1.35) than other obesity types. Permanent night workers demonstrated a 29% higher risk than rotating shift workers (odds ratio 1.43 vs . 1.14). Conclusion: This meta‐analysis confirmed the risks of night shift work for the development of overweight and obesity with a potential gradient association suggested, especially for abdominal obesity. Modification of working schedules is recommended, particularly for prolonged permanent night work. More accurate and detailed measurements on shift work patterns should be conducted in future research.